Long-term creep behaviour of cast TiAl-Ta alloy. (April 2018) - Lapin, J.; Pelachová, T.; Dománková, M.
Abstract: The long-term creep behaviour of the cast Ti-44.4Al-8.1Ta (at.%) alloy with an initial γ-TiAl(L10 )+α2 -Ti3 Al(D019 ) microstructure was investigated at 700 °C. The alloy shows a remarkable creep resistance. The minimum creep rate is measured to be as low as 1.47 × 10 −10 s −1 and total deformation is only 2.5% after an interrupted 30000 h creep test at 200 MPa. The creep exposure affects the stability of the initial microstructure. The discontinuous precipitation leads to the formation of γ + τ(Ti3 Al2 Ta) type of microstructure along the lamellar colony and grain boundaries. The decomposition of the α2 phase results in the formation of τ and γ + α2  + L12 segments within the lamellae and cellular γ + α2  + L12 network within the coarse particles. The intensive formation and coalescence of the cavities along the grain boundaries leads to predominantly intergranual type of creep fracture at the applied stresses of 250 and 300 MPa. Graphical abstract: Image 1 Highlights: The Ti-44.4Al-8.1Ta (at.%) alloy shows a remarkable creep resistance at 700 °C. The τ(Ti3 Al2 Ta) particles are formed by discontinuous precipitation along lamellar colony and grain boundaries. The transformation of the α2 (Ti3 Al) to the γ(TiAl) phase follows two consecutive steps: α2 (D019 ) → Ti3 Al(L12 ) → γ(L10 ). The intensive growth of cavities leads to predominantly intergranual type of fracture.